Long-term clinical course of anti-glycyl tRNA synthetase (anti-EJ) antibody-related interstitial lung disease pathologically proven by surgical lung biopsy. Issue 1 (December 2016) - Sasano, Hajime; Hagiwara, Eri; Kitamura, Hideya; Enomoto, Yasunori; Matsuo, Norikazu; Baba, Tomohisa; Iso, Shinichiro; Okudela, Koji; Iwasawa, Tae; Sato, Shinji; Suzuki, Yasuo; Takemura, Tamiko; et al.
Abstract Background Anti-glycyl-tRNA synthetase (anti-EJ) antibody is occasionally positive in patients with interstitial lung disease (ILD). We aimed to define the clinical, radiological and pathological features of patients with anti-EJ antibody-positive ILD (EJ-ILD). Methods We retrospectively analyzed the medical records of 12 consecutive patients with EJ-ILD who underwent surgical lung biopsy. Results The median follow-up time was 74 months (range, 17–115 months). The median age was 62 years (range, 47–75 years). Seven of 12 patients were female. Eight patients presented with acute onset. Six patients eventually developed polymyositis/dermatomyositis. On high-resolution computed tomography, consolidation and volume loss were predominantly observed in the middle or lower lung zone. Nine patients presented pathologically nonspecific interstitial pneumonia with organizing pneumonia, alveolar epithelial injury and prominent interstitial cellular infiltrations whereas the other three patients were diagnosed with unclassifiable interstitial pneumonia. Although all patients but one improved with the initial immunosuppressive therapy, five patients relapsed. When ILD relapsed, four of the five patients were treated with corticosteroid monotherapy. Four of the six patients without relapse have been continuously treated with combination therapy of corticosteroid and immunosuppressant. Conclusions Patients with EJ-ILD often had acute onset of ILD with lower lung-predominant shadows and pathologically nonspecific interstitial pneumonia or unclassifiable interstitial pneumonia with acute inflammatory findings. Although the disease responded well to the initial treatment, relapse was frequent. Because of the diversity of the clinical courses, combination therapy of corticosteroid and immunosuppressant should be on the list of options to prevent relapse of EJ-ILD.